Pronunciation of English velar nasal (angma) by undergraduate students in Pakistani universities - Afia Mahmood; Humaira Irfan; Nurah Saleh Fares; Shafqat Yasmeen (Universitas Syiah Kuala, 2023)
Pakistani English (PakE) is an emerging variety of English that is in the process of developing its own norms and standards. Besides, distinguishing lexical and syntactic structures, it also has unique phonological features (Baumgardner, 1993; Hassan, 2004; Rahman 1991). Many Pakistani linguists have discussed unique consonantal and vocalic features of Pakistani English (PakE). However, there has not been any significant research conducted on the pronunciation of English velar nasal or angma /ŋ/ by Pakistani English speakers. This study analyses the pronunciation of English velar nasal by Pakistani English speakers. The sample was selected from 20 undergraduate students of the Department of English studying in the first semester of a large-scale public sector university located in Lahore, Punjab, Pakistan. A number of 20 English lexical items were selected and were divided into three categories according to the distribution of angma in the English language. The items were presented to the participants in diagnostic sentences. PRAAT, the speech and phonetics analysis software, was used to analyse the data. The findings revealed that Pakistani English speakers pronounce angma inaccurately in the medial position and insert velar plosive /ɡ/ in the poly-morphemic words. However, in the final position, angma is pronounced correctly by most Pakistani English speakers. The findings highlight that Pakistani English speakers are not concerned about the morpheme boundary and pronounce angma without /ŋɡ/ coalescence. Thus, it is found that Pakistani English speakers have distinguished pronunciation. The study recommends more research on Pakistani English pronunciation as well.